2009
DOI: 10.1212/01.wnl.0000333247.51383.43
|View full text |Cite
|
Sign up to set email alerts
|

Declining brain glucose metabolism in normal individuals with a maternal history of Alzheimer disease

Abstract: Background:At cross-section, cognitively normal individuals (NL) with a maternal history of late-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
175
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(185 citation statements)
references
References 35 publications
6
175
0
2
Order By: Relevance
“…Over a two-year follow-up, CMRglc impairment in maternal AD individuals was found to be progressive [69], with longitudinal CMRglc reductions in the posterior cingulate/precuneus, parietotemporal and frontal cortices. In contrast, individuals with an AD-affected father and those with no family history of AD showed longitudinal CMRglc reductions only in the frontal cortex, which is a typical effect of aging.…”
Section: Fdg Pet and Apoe-associated Genetic Riskmentioning
confidence: 96%
“…Over a two-year follow-up, CMRglc impairment in maternal AD individuals was found to be progressive [69], with longitudinal CMRglc reductions in the posterior cingulate/precuneus, parietotemporal and frontal cortices. In contrast, individuals with an AD-affected father and those with no family history of AD showed longitudinal CMRglc reductions only in the frontal cortex, which is a typical effect of aging.…”
Section: Fdg Pet and Apoe-associated Genetic Riskmentioning
confidence: 96%
“…Cellular bioenergetics at the level of the mitochondrion is intimately linked to glucose metabolism through the provision of pyruvate as a substrate for respiration and NADPH for protection against oxidative stress. Importantly, glucose metabolism is altered in stroke and neurodegenerative diseases, [33][34][35][36][37] emphasizing the need for understanding the potential link between cellular bioenergetics, autophagy and neuronal viability. In support of this concept, our published studies in differentiated SH-SY5Y neuroblastoma cells have shown that HNE decreases mitochondrial function and glycolysis, and can cause cell death.…”
Section: Basic Research Papermentioning
confidence: 99%
“…In the present article, we extend these prior findings by investigating the longitudinal effect of FH and APOE4 on brain morphometry within this cohort, with a particular focus on temporoparietal regions that are now known to be vulnerable to AD pathology. 16,17 In addition, because it has recently been shown that the sex of the ADaffected parent may be influential, with maternal FH being more deleterious, 5,7,8,18 we conducted supplementary analyses to determine whether any observed FH effects were possibly driven by maternal FH. In parallel analyses, we also investigated the effect of FH and APOE4 on cognitive decline.…”
mentioning
confidence: 99%